Building defects: possible solution for poor construction workmanship - Azlan Shah Ali,; Kam , Hui Wen (Penerbit UKM, 2011)
This paper aims to investigate workmanship quality performance of construction projects referring to number of defects occurred for new completed building. The research objectives are the factors contribute to poor workmanship and possible measures to minimise the problem, and also the relationship between measures identified with the factors. Based on a combination of literature review and questionnaire surveys, this paper explores the factors contribute to poor workmanship and possible measures to minimise the problem, and also the relationship between measures identified with the factors. A quantitative research was conducted by sending 75 sets of questionnaire to the respondents who experienced in construction projects. The results from 30 sets of completed questionnaire were used for the quantitative analysis. This paper concludes that construction projects suffered from low quality of workmanship produced by the contractors. The most significant factor contributing to poor workmanship is lack of experience and competency of labours. Correlation test result shows that the significant factor can be sovled by providing training and education to the labours, well manpower management and proper design. This paper singles out the factors contributing to poor workmanship and possible measures that can be implemented by contractors. This would help the contractors improve quality performance on their construction projects.